Fostering a culture of innovation : Leading a company through change brings its own challenges, and requires executives to create an environment that allows innovation to flourish without impediment. (MIT Sloan Management Review, 2018)
"What does it take to make an organization truly innovative? This collection of articles from MIT Sloan Management Review examines the deliberate processes managers can take to nurture innovation and the importance of being able to translate the language of innovators to the executive office."--Resource description page